1979
DOI: 10.1177/00220345790580031101
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Fatigue Limits of Composite Restorative Materials

Abstract: Compressive fatigue limits at 5,000 stress cycles have been measured for seven commercial composite restorative materials. The average of the ratios between fatigue limit and compressive strengths is 0.64.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0
5

Year Published

1981
1981
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 6 publications
3
105
0
5
Order By: Relevance
“…The cyclic shear bond strength (CSBS) data were analyzed according to the design by Draughn. 16 Student's t-test was used to determine significance between the cyclic subgroups and between static and cyclic groups. A Kruskal-Wallis test was used in conjunction with a Mann-Whitney test to compare the differences in the ARI scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cyclic shear bond strength (CSBS) data were analyzed according to the design by Draughn. 16 Student's t-test was used to determine significance between the cyclic subgroups and between static and cyclic groups. A Kruskal-Wallis test was used in conjunction with a Mann-Whitney test to compare the differences in the ARI scores.…”
Section: Discussionmentioning
confidence: 99%
“…For accurate data analysis, a minimum of fifteen samples is required to perform the up and down test to evaluate the fatigue strength. 16 In the present study, the number of each sample group was 25. According to the procedure addressed by Draughn, 16 the data analysis was based on the event that occurred (bond failures, no bond failures) with the least frequency.…”
Section: The Cyclic Fatigue Testingmentioning
confidence: 96%
See 1 more Smart Citation
“…Early fatigue tests focused almost exclusively on restorative materials such as amalgam and resin composites [49][50][51][52][53] . To determine the feasibility of a complex dental restoration, Huysmans et al 52) employed a fatigue testing machine (load cycling at 5 Hz frequency) to evaluate the mechanical fatigue behavior of premolar teeth restored with a titanium alloy post and an amalgam or composite core.…”
Section: Load Cycling Fatigue Test Of Prg Filler-filled Adhesivesmentioning
confidence: 99%
“…Fatigue studies showed a correlation between the compressive strength and the fatigue limit, indicating that a composite with a high compressive strength will withstand fatigue better 20) . PM2 demonstrated higher compressive strength than PM0 in both DRY and WET groups.…”
Section: Discussionmentioning
confidence: 99%